Deployment characterization of a floatable tidal energy converter on a tidal channel, Ria Formosa, Portugal - Pacheco, André (2018)
This paper presents the results of a pilot experiment with an existing tidal energy converter (TEC), Evopod 1 kW floatable prototype, in a real test case scenario (Faro Channel, Ria Formosa, Portugal). A baseline marine geophysical, hydrodynamic and ecological study based on the experience collected on the test site is presented. The collected data was used to validate a hydro-morphodynamic model, allowing the selection of the installation area based on both operational and environmental constraints. Operational results related to the description of power generation capacity, energy capture area and proportion of energy flux are presented and discussed, including the failures occurring during the experimental setup. The data is now available to the scientific community and to TEC industry developers, enhancing the operational knowledge of TEC technology concerning efficiency, environmental effects, and interactions (i.e. device/environment). The results can be used by developers on the licensing process, on overcoming the commercial deployment barriers, on offering extra assurance and confidence to investors, who traditionally have seen environmental concerns as a barrier, and on providing the foundations whereupon similar deployment areas can be considered around the world for marine tidal energy extraction.